2021
DOI: 10.1186/s12902-021-00877-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of vitamin D deficiency and its associated risk factors among rural population of the northern part of the Persian Gulf

Abstract: Background Accumulating evidence indicates that vitamin D deficiency has been increased globally over the last two decades. However, the majority of these studies are concerned with cities and there is scant information regarding the prevalence of vitamin D in rural areas. The main aim of this study was to investigate the prevalence of vitamin D deficiency and its associated risk factors among the rural population in Bushehr province which shares the longest border with the Persian Gulf. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
0
3
0
2
Order By: Relevance
“…Pereira-Santos et al ( 37 ) reported that 28.16% of Brazilians suffered from VDD when using a cut-off of 50 nmol/L, higher than the result of our study (24.6%). It could mean that other factors besides latitude or sun exposure may affect vitamin D status, like race/ethnicity, cultural practices, and other factors ( 38 , 39 ). For instance, in the United States, food supplementation and fortification are common sources of vitamin D ( 40 ), but they are unavailable in many African and South American countries ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pereira-Santos et al ( 37 ) reported that 28.16% of Brazilians suffered from VDD when using a cut-off of 50 nmol/L, higher than the result of our study (24.6%). It could mean that other factors besides latitude or sun exposure may affect vitamin D status, like race/ethnicity, cultural practices, and other factors ( 38 , 39 ). For instance, in the United States, food supplementation and fortification are common sources of vitamin D ( 40 ), but they are unavailable in many African and South American countries ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…There was a negative association between age and vitamin D status, in which younger individuals had identified they were vitamin D deficient. Marzban et al ( 47 ) observed that participants ( n = 1,806) who were between the ages of 30–39 had lower serum vitamin D levels compared to participants who were 80 years and older. This was further confirmed by analyses of NHANES data ( n = 25,010) that showed 42.4% of individuals between the ages of 18–39 years old were vitamin D deficient compared to 21.0% of individuals aged 60 years and older ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hal ini diduga akibat perubahan gaya hidup dan pada masyarakat setempat sehingga peningkatan makanan sumber vitamin D dan suplemen tambahan direkomendasikan untuk mengatasi permasalahan ini. 25 Hasil yang berbeda pada penelitian ini bisa disebabkan karena adanya perbedaan pada jenis makanan. Jenis-jenis makanan yang ditanyakan pada kuesioner penelitian ini merupakan jenis makanan yang universal.…”
Section: Pembahasanunclassified
“…Sumber makanan utama yang kaya akan vitamin D berbeda tergantung kebiasaan makan dan kebijakan gizi di masing-masing negara, misalnya di negara Amerika dan Kanada sumber utamanya berupa susu, daging dan ikan, di Britania Raya berupa daging, produk olahan daging, lemak dan sereal, di Jepang berupa ikan, telur dan jamur. 13 Temuan-temuan tadi mengindikasikan bahwa asupan vitamin D tidak selalu mencerminkan konsentrasi vitamin D dalam serum tetapi tetap dapat dijadikan suatu skrining risiko defisiensi vitamin D. [25][26][27]…”
Section: Pembahasanunclassified